The impact of the socio-economic crisis of 2001 on the scientific system of Argentina from the scientometric perspective - Miguel, Sandra (Scientometrics.)
Abstract In recent years a number of studies have focused on Argentina's 2001 economic crisis and its political, social, and institutional repercussions. To date, however, no studies have analyzed its effects upon the country's scientific system from a scientometric perspective, in terms of resources dedicated to scientific activity and the final output and impact. The present study does so by means of a set of scientometric indicators that reflect economic effort, human resources dedicated to research, publications, collaborative relations, and the international visibility of scientific contributions